Public health and tropical modernity: the combat against sleeping sickness in Portuguese Guinea, 1945-1974 - Philip Jan Havik (História, Ciências, Saúde: Manguinhos)
Until the establishment of the “Commission for the study of and combat against sleeping sickness” (Missão de estudo e combate à doença do sono) in 1945, underfunded and understaffed health services had not been a priority for the colonial administration in Portuguese Guinea. The Commission not only implemented endemic disease control in the territory under the auspices of metropolitan institutions, but also provided preventive public healthcare to the local population. Its relative success in reducing the negative impact of Human African Trypanosomiasis turned the colony into an apparent model of tropical modernity. In the process, the local evolution of the disease was marginalized, despite the tacit but contested recognition by some health professionals of the role of popular healthcare.